2017
DOI: 10.1021/acs.est.7b03464
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Lithium from Geothermal Brine with Lithium–Aluminum Layered Double Hydroxide Chloride Sorbents

Abstract: We report a three-stage bench-scale column extraction process to selectively extract lithium chloride from geothermal brine. The goal of this research is to develop materials and processing technologies to improve the economics of lithium extraction and production from naturally occurring geothermal and other brines for energy storage applications. A novel sorbent, lithium aluminum layered double hydroxide chloride (LDH), is synthesized and characterized with X-ray powder diffraction, scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(78 citation statements)
references
References 18 publications
0
73
0
1
Order By: Relevance
“…A recent absorption experiment using Li-LDH has found that 91% of the lithium was recovered from a geothermal brine solution with high selectivity over Na and K ions. 13 This selectivity arises because the larger alkali ions cannot be accommodated in the octahedral sites of the LDH structure. The economic viability of the sorbent is improved through its reversibility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent absorption experiment using Li-LDH has found that 91% of the lithium was recovered from a geothermal brine solution with high selectivity over Na and K ions. 13 This selectivity arises because the larger alkali ions cannot be accommodated in the octahedral sites of the LDH structure. The economic viability of the sorbent is improved through its reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that if LiCl is less than 125 mg/L in the stripping solution, the LDH phase decomposes to the Al(OH) 3 phase. 13 In addition, when the LiCl concentration is more than 360 mg/L, the LDH becomes saturated and no further absorption occurs. 13 In addition to defining the capacity for Li ions, the stability of the LDH phases controls the cycling life and lithium recovery efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitrakar et al. found that the adsorption capacity of H 1.33 Mn 1.67 O 4 and H 1.6 Mn 1.6 O 4 reached up to 30.0 mg g −1 . Furthermore, the crystal structure of LMO only matches the size of Li + , giving a distinct “lithium ion‐sieve effect,” that is, the large‐sized Na + , K + , and Ca 2+ cannot enter.…”
Section: Introductionmentioning
confidence: 99%
“…[23,[28][29][30] During lithium insertion/extraction, the spinel-type of HMO is well maintained, guaranteeing it to be a long-term lithium adsorbent with high selectivity and high adsorption capacity. Chitrakar [31,32] Furthermore, the crystal structure of LMO only matches the size of Li + , giving a distinct "lithium ion-sieve effect," that is, the large-sized Na + , K + , and Ca 2+ cannot enter. Although Mg 2+ shows similar ionic radius to Li + , its hydration free energy is four times of that of Li + .…”
Section: Introductionmentioning
confidence: 99%